2016
DOI: 10.21162/pakjas/16.4823
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Local and Exotic Sugarcane Genotypes on the Basis of Morphological and Quality Related Attributes

Abstract: The current breeding program of sugarcane in Pakistan does not fulfill the variety evolution of desired characters. It mostly depends on import of exotic fuzz-seed of sugarcane varieties, without keeping varietal characters in view. So, it is the dire need of the time to characterize the sugarcane germplasm not only for saving resources but also for finding genetic relationships among breeding materials for overall sugarcane crop improvement. In the present study 60 genotypes of sugarcane, belonged to 3 resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…shows the more than 90% of total variation (Table 4 ).Our findings are in conformity with Shahzad et al (2016), Ahmed and Gardezi, (2017), Aamer et al (2018) and Khan et al (2019).…”
Section: Principle Component and Bi-plot Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…shows the more than 90% of total variation (Table 4 ).Our findings are in conformity with Shahzad et al (2016), Ahmed and Gardezi, (2017), Aamer et al (2018) and Khan et al (2019).…”
Section: Principle Component and Bi-plot Analysissupporting
confidence: 92%
“…It is largely reliant on the introduction of exotic fuzz-seed sugarcane types, with little regard for varietal characteristics. As a result, characterising sugarcane germplasm is critical not just for resource conservation but also for identifying genetic linkages across breeding materials for overall sugarcane crop improvement (SHAHZAD et al, 2016). Taking into account foregoing research work, the present study was planned to evaluate sugarcane germplasm for yield traits in response to sugarcane red rot severity under natural filed condition with ultimate objective to search out sugarcane red rot free genotypes having high yield to secure sugarcane crop and their supplementary utilization in sugarcane breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…China is one of the main sugar producers in the world while Guangxi is the largest sugarcane and sugar-producing area in China, whose sugar production accounts for more than 60% of the total in China [ 8 ]. Sugar yield is a quantitative character which depends upon cane yield, sucrose content and sugar recovery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty eight superior interspecific hybrids with high index score for agronomic traits and wider inter cluster distance were identified as pre breeding stocks and utilized in further backcross programmes In this study, we used the Principal Component Analysis (PCA) and identified five traits for phenotypic characterization of sugarcane, and there by to select superior clones in the breeding process. Kang et al (2013), Ongala et al (2016), Shahzad et al (2016) and Mehrabeb et al (2020) in their studies identified most of the yield traits to be significant in identifying the superior clones and their contribution to the selected traits. The pattern of expression of genotypes in each PCs and environment varied.…”
Section: Resultsmentioning
confidence: 99%